Korean women: breast cancer knowledge, attitudes and behaviors - Sadler, Georgia R (BioMed Central, 2001)
INTRODUCTION: Clustered within the nomenclature of Asian American are numerous subgroups, each with their own ethnic heritage, cultural, and linguistic characteristics. An understanding of the prevailing health knowledge, attitudes, and screening behaviors of these subgroups is essential for creating population-specific health promotion programs. METHODS: Korean American women (123) completed baseline surveys of breast cancer knowledge, attitudes, and screening behaviors as part of an Asian grocery store-based breast cancer education program evaluation. Follow-up telephone surveys, initiated two weeks later, were completed by 93 women. RESULTS: Low adherence to the American Cancer Society's breast cancer screening guidelines and insufficient breast cancer knowledge were reported. Participants' receptiveness to the grocery store-based breast cancer education program underscores the importance of finding ways to reach Korean women with breast cancer early detection information and repeated cues for screening. The data also suggest that the Asian grocery store-based cancer education program being tested may have been effective in motivating a proportion of the women to schedule a breast cancer screening between the baseline and follow-up surveys. CONCLUSION: The program offers a viable strategy to reach Korean women that addresses the language, cultural, transportation, and time barriers they face in accessing breast cancer early detection information.